HUBUNGAN PERSEPSI KOMPENSASI TERHADAP KINERJA BIDAN DESA DALAM PELAKSANAAN PROGRAM KELAS IBU HAMIL DI PUSKESMAS KABUPATEN PURBALINGGA - Happinasari, Ossie; Jati, Sutopo Patria; Kartini, Apoina (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
The implementation of women pregnat class inpurbalingga is not optimum because the village midwife has low performance in theimplemantation of KIH. KIH program has been sosialized in purbalingga since 2011. On2012 there are 22 health services in the regional service of purbalingga healthdepartment are not held the KIH.The purpose of the study was to determine the influenceof compensation on the performance of village midwife in the implementation of pregnantwomen class in Purbalingga Regional Health Services. Design of the study wasobservational analytic with cross sectional approach. The research instrument using astructured questionnaire. Data was collected through interviews. The population in thisÂ study were 225 midwives who work in the area of Occupational Health Services ofPurbalingga, who had been carrying out of pregnant women classes midwife in 165times. Proportional sampling technique using purposive sampling with a sample of 63respondents. Bivariate analysis performed by chi square test. The results showed that themidwife has a good compensation perception (52.4%). The results of bivariate analysisshowed that perception of compensation (p = 0.032) is positively related to theperformance of the midwife in the implementation class for pregnant women. It isrecommended to the Health Department of Purbalingga Regency make a detailedschedule of supervision appropriate to the pregnant women class program on the Kesgadepartment. Health Service make a schedule regularly to the meetings between the headof the health service and midwife in order to coordinate the class program for pregnantwomen.Keywords: Compensation perception, midwife, the pregnant women class